THE EFFECT OF STUDENT’S METACOGNITION ABILITY TO THEIR REASONING BY USING REALISTIC MATHEMATICAL EDUCATION APPROACH AT SECONDARY SCHOOL OF UNGGUL SAKTI JAMBI - Sri Dewi (Universitas Batanghari Jambi, 2015)
Based on observation so far, learning process in the classroom only could impacted a little to the students metacognition ability and their mathematical reasoning. Metacognition ability is an ability of a student in controlling way of thinking and their ability to use strategy needed to understand the concept of previous knowledge. Reasoning is thinking ability to reflex the framework of certain based on the concept of understanding that they have learnt. To develop those both capacity and adapted it to material learned, one of them is by using realistic mathematical education approach. This research was aimed to understand the effect of metacognition ability to students reasoning by using realistic mathematical education approach. The method used in this research was quasi experimental method, subject of this research is student at VIII class from secondary school of Unggul sakti. Random sampling technique was used to decide class VIII F as a experiment class and class VIII E as control class.Result of the experiment showed that there were linear correlation r = 0,978142 with coefficient determination r2 = 0.989011 or as much 98,9 % gain tcount = 24,44271 and ttabel = t0,975 = 2,052 with significant level α = 0,05. From the calculation it showed that tcount > ttabel it means that Hypotheses (H1) accepted. Based on the final result it could be conclude that metacognition ability affect student reasoning by using realistic mathematical education approach.Keywords : Metacognition, Mathematical Reasoning, Realistic Mathematical Education